A Novel One-Pot and One-Step Microwave-Assisted Cyclization-Methylation Reaction of Amino Alcohols and Acetylated Derivatives with Dimethyl Carbonate and TBAC - Adrián Ochoa-Terán; Leticia Guerrero; Ignacio A. Rivero (The Scientific World Journal)
A simple and efficient microwave-assisted methodology for the synthesis of 4-substituted-3-methyl-1,3-oxazolidin-2-ones from amino alcohols catalyzed by a ionic liquid was developed. This novel one-pot and one-step cyclization-methylation reaction represents an easier and faster method than any other reported protocols that can be used to obtain the desired products in good yields and high purity. Applying microwave irradiation at 130°C in the presence of TBAC, dimethyl carbonate acts simultaneously as carbonylating and methylating agent and surprisingly promotes an in situ basic trans esterification when a N-acetylated amino alcohol is used as starting material. Furthermore, dimethyl carbonate worked better than diethyl carbonate in performing this reaction.